Why not in your backyard?: on the location and size of a public facility - Giorgio Bellettini; Hubert Kempf (Center for Economic Studies and ifo Institute (CESifo), 2008)
In this paper, we tackle the issue of locating a public facility which provides a public good in a closed and populated territory. This facility generates differentiated benefits to neighborhoods depending on their distance from it. In the case of a Nimby facility, the smaller is the distance, the lower is the individual benefit. The opposite is true in the case of an anti-Nimby facility. We first characterize the optimal location which would be chosen by a social planner. Then we introduce a common-agency lobbying game, where agents attempt to influence the location and provision decisions by the government. Some interesting results arise in the case where only a subset of neighborhoods lobby. First, the solution of the lobbying game can replicate the optimal solution. Second, under-provision and over-provision of the public good may be obtained both in the Nimby and the anti-Nimby cases. The provision outcome depends on the presence of either a congestion effect or an agglomeration effect. Third, some non-lobbying neighborhoods may be better off than in the case where all neighborhoods lobby, which raises the possibility of free-riding at the lobbying stage.
Keywords: R00; 330; Öffentliche Einrichtung; Standortwahl; Öffentliches Gut; Externer Effekt; Interessenpolitik; Public Choice; Spieltheorie; Theorie